Key Taxa of the Gut Microbiome Associated with the Relationship Between Environmental Sensitivity and Inflammation-Related Biomarkers - Satoshi Takasugi; Shuhei Iimura; Miyabi Yasuda; Yoshie Saito; Masashi Morifuji (Microorganisms)
Individual differences in environmental sensitivity are linked to stress-related psychiatric symptoms. In previous research, we found that high environmental sensitivity can be a risk factor for increased inflammation and gut permeability, particularly when gut microbiome diversity is low. However, the specific gut bacterial taxa involved in this interaction remain unclear. As a preliminary study, this research aimed to identify the key gut microbiome taxa associated with this relationship. Environmental sensitivity, gut microbiome composition, gut permeability (lipopolysaccharide-binding protein, LBP), and inflammation (C-reactive protein, CRP) biomarkers were evaluated in 88 participants. The interaction between environmental sensitivity and the relative abundance of the family Marinifilaceae (genus Butyricimonas) was a predictor of CRP levels. Similarly, the interaction between environmental sensitivity and relative abundance of the family Barnesiellaceae (genus Coprobacter), the family Akkermansiaceae (genus Akkermansia), the genus Family XIII AD3011 group, the genus GCA-900066225, or the genus Ruminiclostridium 1 predicted LBP levels. Individuals with high environmental sensitivity exhibited elevated CRP or LBP levels when the relative abundance of these taxa was low. Conversely, highly sensitive individuals had lower CRP or LBP levels when the relative abundance of these taxa was high. This study suggests that specific taxa serve as one of the protective factors against inflammation and gut permeability in individuals with high environmental sensitivity. Further in-depth studies are needed to confirm these associations and understand the underlying mechanisms.